Comparison of Clinical Outcome between Craniectomy and Craniotomy as Surgical Management of Traumatic Acute Subdural Hematoma: A Systematic Review and Meta-analysis - Mahadewa, Tjokorda Gde Bagus; Mardhika, Putu Eka; Maliawan, Sri; Golden, Nyoman; Awyono, Steven; Ryalino, Christopher (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Acute subdural hematoma (ASDH) is a major problem in traumatic brain injury. Surgical techniques for treating ASDH are varied, including cranioplastic craniotomy and large decompressive craniectomy. The superiority of craniectomy and craniotomy for treating ASDH is still controversial. AIM: The aim of this study was to compare the clinical outcome between craniectomy and craniotomy for treating traumatic ASDH through systematic review and meta-analysis. METHODS: This study used electronic articles published in PubMed, EBSCO, Google Scholar, and Directory of Open Access Journal. Articles included were full-text observational studies in Indonesian or English. Clinical outcome using the Glasgow Outcome Scale was compared between craniectomy and craniotomy. Statistical analysis was done using Review Manager 5.3. RESULTS: Six articles met our inclusion and exclusion criteria. We performed random effect model analysis because of high heterogeneity between studies (I2 = 77%; X2 = 21.98). The pooled risk ratio between craniectomy and craniotomy on poor outcomes was 1.41 (p = 0.02; 95% CI: 1.06–1.88). CONCLUSION: Craniectomy increases the risk of poor clinical outcomes in treating a traumatic ASDH.